2016
DOI: 10.1103/physrevc.94.024919
|View full text |Cite
|
Sign up to set email alerts
|

Initial-state fluctuations in collisions between light and heavy ions

Abstract: In high energy collisions involving small nuclei (p+p or x+Au collisions where x=p, d, or 3 He) the fluctuating size, shape and internal gluonic structure of the nucleon is shown to have a strong effect on the initial size and shape of the fireball of new matter created in the collision. A systematic study of the eccentricity coefficients describing this initial fireball state for several semi-realistic models of nucleon substructure and for several practically relevant collision systems involving small nuclei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 88 publications
5
79
0
Order By: Relevance
“…1-2, within wounded quark models. These studies lead to the correct negative sign of SC(2,3) at high multiplicities but the magnitude is off [18][19][20]. Also without hydrodynamic evolution, qualitative agreement with the p+Pb results has been achieved in an initial state model where the partons in the projectile coherently scatter off the color fields in the heavy nuclear target [21,22].…”
Section: Introductionmentioning
confidence: 93%
“…1-2, within wounded quark models. These studies lead to the correct negative sign of SC(2,3) at high multiplicities but the magnitude is off [18][19][20]. Also without hydrodynamic evolution, qualitative agreement with the p+Pb results has been achieved in an initial state model where the partons in the projectile coherently scatter off the color fields in the heavy nuclear target [21,22].…”
Section: Introductionmentioning
confidence: 93%
“…Quantitative hydrodynamic predictions of azimuthal correlations in pp and pPb systems still have large uncertainties, mainly due to limited knowledge of initial-state fluctuations of energy deposition at sub-nucleonic scales [35][36][37]. Detailed modeling of initial-state fluctuations in pp and pPb collisions [38] can be further constrained by the study of v n coefficient correlations. For example, a positive correlation between v 2 and v 3 is predicted in pp collisions over the full multiplicity range [38], the opposite to what is observed in PbPb collisions [18].…”
mentioning
confidence: 99%
“…Detailed modeling of initial-state fluctuations in pp and pPb collisions [38] can be further constrained by the study of v n coefficient correlations. For example, a positive correlation between v 2 and v 3 is predicted in pp collisions over the full multiplicity range [38], the opposite to what is observed in PbPb collisions [18]. Measuring v n correlations in small colliding systems will help to understand if a common paradigm to describe collectivity in all hadronic systems can be found.This Letter presents high precision measurements of anisotropy coefficients v 4 in pp at √ s = 13 TeV, pPb at √ s NN = 8.16 TeV, and PbPb at √ s NN = 5.02 TeV using data from the CMS experiment.…”
mentioning
confidence: 99%
“…We note that the focus of this paper has been on small scale structure in large PbPb collisions. Recently, it has been shown that small systems such as pPb and pp may provide more clues about small scale structure [35,[81][82][83][84]. We leave a deeper study on small systems for a later work.…”
Section: Discussionmentioning
confidence: 99%